Terminologia e Internacionalização: equivalência português/inglês das disciplinas de Letras da Unioeste - Stemposki Filho, Marcelo (2023)
The sharing of scientific knowledge among Higher Education institutions from different countries has been massively intensified, particularly in the last decade. The process of internationalization is present to meet the demands of dialogue between researchers and students from different institutions who engage in scientific information exchanges and promote mutual collaboration and development, thus strengthening the international scientific community. As this process often occurs between institutions from countries or continents that use different languages, a standard language needed to be established as a communicative bridge. Due to various geopolitical and cultural reasons, English is currently the global lingua franca in the academic world; therefore, a significant portion of international communication takes place in this language. To expand the participation of the Brazilian academic community in this context, it is recommended to take certain measures to promote it. Inclusion in the internationalization process can range from encouraging students to participate in Academic Mobility programs to reviewing their documentation, which, among various procedures, must be presented in a foreign language. In light of this context, the question arises: what could be the nomenclature of the disciplines in the undergraduate programs in Language Studies at Unioeste in English, suitable for bilingual academic documentation? Thus, this study aims to propose, as its general objective, the nomenclature of the disciplines in the undergraduate Language Studies programs at Unioeste in English, with a view to adapting their academic documentation to a bilingual perspective. The specific objectives are to understand the process of internationalization in Brazilian universities, conduct a documentary survey of the syllabi of the Language Studies programs at Unioeste as well as from selected American universities, and investigate the syllabi of the selected courses, analyzing the terms that can be equivalent or correspondent in the bilingual perspective of the corpus. The adopted methodology is Corpus Linguistics (CL) using the Sketch Engine tool. The corpus consists of the Pedagogical Political Projects of the Language Studies programs at Unioeste and the course catalogs of three well-ranked American universities in terms of internationalization. The research is based on elementary studies by authors in the field of Terminology such as Krieger and Finatto (2020), Barros (2004), and Bevilacqua and Tagnin (2013), which deal with corpora in terminological research. As theoretical support from the field of internationalization, we relied on the works of Knight and De Wit (1997), Hudzik and McCarthy (2012), and Santos and Almeida Filho (2012), which address the role of internationalization in the university's role in the information society. As a result of the analysis of the syllabi of the Language Studies programs at Unioeste and the selected foreign institutions, out of the 81 analyzed disciplines, 23 have equivalents in English in the corpus, 39 have correspondents, and 19 do not have equivalents or correspondents. The study also showed that foreign universities tend not to use serial nomenclature for some disciplines, such as foreign languages.